Ketamine-Assisted and Culturally Attuned Trauma Informed Psychotherapy as Adjunct to Traditional Indigenous Healing: Effecting Cultural Collaboration in Canadian Mental Health Care - Sherry-Anne Muscat; Geralyn Dorothy Wright; Kristy Bergeron; Kevin W. Morin; Courtenay Richards Crouch; Glenn Hartelius (Behavioral Sciences, 2021)
Ketamine therapy with culturally attuned trauma-informed psychotherapy in a collaborative cross-cultural partnership may provide a critical step in the operationalization and optimization of treatment effectiveness in diverse populations and may provide a foundation for an improved quality of life for Indigenous people. Decolonizing Indigenous health and wellbeing is long overdue, requiring an equal partnership between government and Indigenous communities, built upon an aboriginal culture holistic foundation of balance of mind, body, social and spiritual realms, and within the context of historical and lived experiences of colonialism. Culturally attuned trauma-informed psychotherapy paired with ketamine—a fast-acting antidepressant that typically takes effect within 4 hours, even in cases of acute suicidality—may be uniquely qualified to integrate into an Indigenous based health system, since ketamine’s therapeutic effects engage multiple neuropsychological, physiological, biological, and behavioral systems damaged by intergenerational complex developmental trauma. Ketamine holds the potential to serve as a core treatment modality around which culturally engaged treatment approaches might be organized since its brief alteration of normal waking consciousness is already a familiar and intrinsic element of healing culture in many Indigenous societies. There is great need and desire in Indigenous communities for respectful and sacred partnership in fostering more effective mental health outcomes and improved quality of life.